Highly stable RGD/disulfide bridge-bearing star-shaped biodegradable nanocarriers for enhancing drug-loading efficiency, rapid cellular uptake, and on-demand cargo release - Yan J (Dove Medical Press, 2018)
Jianqin Yan,1,* Hai Zhang,1,* Furong Cheng,1 Yanmei He,1 Ting Su,1 Xuequan Zhang,2 Man Zhang,2 Yutong Zhu,3 Congrui Li,3 Jun Cao,1 Bin He1 1National Engineering Research Center for Biomaterials, Sichuan University, Chengdu 610064, China; 2College of Chemical Engineering, Sichuan University, Chengdu 610065, China; 3College of Chemistry, Sichuan University, Chengdu 610065, China *These authors contributed equally to this work Background: Stability, enhanced drug-loading efficiency (DLE), and specific accumulation of therapeutics at tumor sites remain major challenges for successful cancer therapy.Purpose: This study describes a newly developed intelligent nanosystem that integrates stealthy, active targeting, stimulus-responsiveness, and π-π interaction properties in a single carrier, based on the multifunctional star-shaped biodegradable polyester.Patients and methods: This highly stable, smart nanocarrier with spherical structures and a low critical micelle concentration (CMC) can provide spacious harbor and strong π–π interaction and hydrophobic interactions for hydrophobic doxorubicin (DOX). Its structure and morphology were characterized by proton nuclear magnetic resonance (1H-NMR) spectra, Fourier transform infrared (FTIR) spectra, Gel permeation chromatography (GPC), dynamic light scattering (DLS), scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Antitumor effciency of polymeric micelles using CCK-8 assay, and the intracellular-activated delivery system was tracked by confocal laser scanning microscopy (CLSM) and flow cytometry.Results: The synthesized copolymer can be self-assembled into nanoparticles with size of 50 nm and critical micellar concentration of 2.10 µg/mL. The drug-loading content of nanoparticles can be enhanced to 17.35%. Additionally, the stimulus-responsive evaluation and drug release study showed that the nanocarrier can rapidly respond to the intracellular reductive environment and dissociate for drug release. An in vitro study demonstrated that the nanocarrier can ferry doxorubicin selectively into tumor tissue, rapidly enter cancer cells, and controllably release its payload in response to an intracellular reductive environment, resulting in excellent antitumor activity in vitro.Conclusion: This study provides a facile and versatile approach for the design of multifunctional star-shaped biodegradable polyester nanovehicles for effective cancer treatment. Keywords: intelligent, star-shaped, biodegradable multifunctional polyester, stimuli-responsiveness, intracellular drug delivery, active targeting, cancer therapy